Combination therapy using molecular‐targeted drugs modulates tumor microenvironment and impairs tumor growth in renal cell carcinoma. (23rd August 2017) - Kitano, Hiroyuki; Kitadai, Yasuhiko; Teishima, Jun; Yuge, Ryo; Shinmei, Shunsuke; Goto, Keisuke; Inoue, Shogo; Hayashi, Tetsutaro; Sentani, Kazuhiro; Yasui, Wataru; Matsubara, Akio
Abstract: Tumor growth and metastasis are determined not by cancer cells alone but also by a variety of stromal cells, various populations of which overexpress platelet‐derived growth factor receptors (PDGF‐Rs). In addition, activation of PI3K‐AKT‐mammalian target of rapamycin (mTOR) signaling is frequently observed in many cancer types as well. mTOR comprises a serine/threonine kinase that increases the production of proteins that stimulate key cellular processes such as cell growth and proliferation, cell metabolism, and angiogenesis. In this study, we investigated the impact of molecular‐targeting agents including PDGF‐R and mTOR inhibitors on the tumor stroma of human kidney cancer and examined the efficacy of combination therapy with these agents against this disease. Treatment with sunitinib did not suppress tumor growth, but significantly decreased stromal reactivity, microvessel density, and pericyte coverage of tumor microvessels in an orthotopic mouse model. In contrast, treatment with everolimus decreased tumor growth and microvessel density but not stromal reactivity. However, sunitinib and everolimus in combination reduced both the growth rate and stromal reaction. These findings suggest that target molecule‐based inhibition of the cancer–stromal cell interaction appears promising as an effective antitumor therapy. Abstract : We showed that aTKI inhibits the cancer stroma of RCC mainly through PDGF signaling pathways, whereas an mTOR inhibitor inhibits cancer cell proliferation, such that the combination therapy effectively inhibits the tumor environment of RCC leading to impaired tumor growth.